A space-coiled acoustic metamaterial with tunable low-frequency sound absorption. (19th February 2018) - Wang, Yang; Zhao, Honggang; Yang, Haibin; Zhong, Jie; Wen, Jihong
Abstract: A novel low-frequency absorber composed a perforated panel and a cavity with a coiled-up channel is presented and demonstrated. Both theoretical analysis and finite element method are utilized to reveal that the absorber possesses a low-frequency absorption with deep-subwavelength thickness. The effect of the folding number of a space-coiled channel on the absorption peak position is discussed and the result shows that a greater folding number can reduce the absorption peak frequency dramatically without sacrificing the total thickness of the absorber. In order to broaden the absorption bandwidth, an absorber combining two units with different folding number is constructed to further enhance the low-frequency absorption performance.